Spacial variability and sampling density of chemical attributes in archaeological black earth and native forest soil in Manicoré, AM - de Oliveira, Ivanildo Amorim [UNESP]; Marques, José [UNESP]; Campos, Milton César Costa; de Aquino, Renato Eleotério [UNESP]; Siqueira, Diego Silva [UNESP]; de Freitas, Ludmila [UNESP] (My University, 2014)
Considering the lack of information about spatial behavior of the soil attributes in areas of archaeological black earth and native forest, the objective of this study was to evaluate the spatial variability of chemical attributes and determine the sampling density in soil with archaeological black earth and native forest in the region of Manicoré, AM. The study was conducted in a rural property located in the community of Santo Antônio do Matupi, at the margins of BR 230, Trans-amazon highway, in the region of Manicoré, AM. In these areas were established grids of 70 m × 70 m, with regular spacing of 10 × 10 m, totaling 64 points, then soil samples were collected at a depth of 0.0-0.20 m and 0, 40-0,60 m. Chemical attributes were determined (pH, OM, P, K, Ca, Mg, SB, CTC, V% and H + Al). Data were analyzed using descriptive statistical techniques and geostatistics. Sampling density was determined basing on CV and on the range of the semivariograms. It was verified that the studied attributes showed spatial variability and the area of archaeological black earth presented greater spatial variability than the native forest. Its greater sampling density was determined basing on the range of the adjusted semivariograms.
Keywords: Attributes of soil; Geostatistics; Indian black earth